(3YdefG QShd Gddg Udi Gddg Ydjg h Sdes (3McGjGJ JQHhjIs - (3aQjO, QjgGe eMeOs; (3YHO GdZaGQ, LeGds; (3YHjO, YHO GdeQVis ((3GdbGgQIs (3SajQs, 2008)
(3YdefG QShd Gddg Udi Gddg Ydjg h Sde (B"(3Ef Gddg jMH EPG Yed CMOce YedkG Cf jJbfg(B" (3CMGOjK YXjeI YdegG dfG QShd Gddg Udi Gddg Ydjg h Sde ceG YdefG ZjQgG GdcKjQ h GdcKjQ dcffG ai cKjQ ef GdCMjGf bO fZad YfgG h dG fJPcQgG ai cKjQ ef CehQ MjGJfGs
(3bUU OjfjIs
3 5 11
Keywords: Islamic Stories; (3GdbUU GdOjfjIs